PEMERIKSAAN PINGGANG DAN SOSIALISASI LATIHAN LUMBOPELVIC STABILIZATION DAN RHYTMIC STABILIZATION MENGURANGI DISABILITAS AKIBAT NYERI PUNGGUNG BAWAH MIOGENIK - Widnyana, M.; Putra, I.P.Y.P.; Kamayoga, I.D.G.A.; Utama, A.A.G.E.S. (Buletin Udayana Mengabdi; Vol 23 No 4 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i04.p08, 2023)
Low back pain (LBP) is pain that occurs due to disorders of muscles and other soft tissues that can cause disability. People in Banjar Malkangin, Dajan Peken Village, Tabanan live from activities that are at risk of causing myogenic NPB. The purpose of this service is to socialize the benefits of doing lumbopelvic stabilization exercise and rhythmic stabilization exercise so that disability is reduced due to myogenic NPB. The specific target of this service activity is that the community recognizes and can conduct exercises as preventive and curative efforts for myogenic NPB cases. The method used is to come directly to do a waist examination and education. The waist examination is carried out through a physical examination and a MODI (Modified Oswestry Disability Index) questionnaire. Education is carried out by the method of socializing pamphlets and simulating exercises. The service activity succeeded in presenting 200 participants. In the results of the waist examination, as many as 50 respondents experienced mild disability, 125 respondents experienced moderate disability and 25 respondents experienced severe disability. The average result of the disability score is 34.30+12.29, which means that residents experience moderate disabilities due to myogenic LBP. The service participants were very enthusiastic, because through this program waist movement health improved, so that disability decreased and productivity could increase.   Keywords : myogenic low back pain, disability, lumbopelvic stabilization, rhythmic stabilization